Properties of empty fruit bunch oil palm (elaeis guineesis) composite boards at different densities and resin contents - Razak Wahab; Siti Marlia Mohd Dom; Mohd Tamizi Mustafa; Hashim W. Samsi; Sukhairi Mat Sasat; Izyan Khalid (2015)
Properties of composite boards made from oil palm Empty Fruit Bunch (EFB) at different density and resin content were investigated. The EFB was refined using fiber cutter and particle's crusher. Hardeners and wax were added at 1 and 3% during the mixing process. Boards of densities 500, 600 and 700 kg m-3 were produced with resin urea formaldehyde at 10, 12 and 14%, respectively. The boards were stored in a conditioning chamber set at 20±2°C and 65% relative humidity before undergoing subsequent testing. Testing procedure was done in accordance with EN Standard and specifications. The results indicated increases across the board physical and mechanical properties. The highest MOR and MOE value achieved in this study were 22.91 and 2059.56 N mm-2. Highest value for internal bonding was 0.98 N mm-2, meanwhile for edge and face screw withdrawal, 467.47 and 512.37 N mm-2. Boards with 700 g cm-3 density and 14% resin content met all the requirement needed according to standard exercised. Board with the lowest performance was observed using microscopy machine to study the resin-fiber bonding property. Resin and fiber in the board intacted closely but there were voids appeared at the cross-section of the board 500 g cm-3 density with 10% resin content, suggesting moisture had penetrated into the board via the open spaces and attacked the linkages existed, thus cause the board to have a low property. Thermogravimetric analysis was done to study the thermal stability of the boards manufactured. The maximum rate of decomposition for the OPEFB boards occurred at 380.83°C.